Health professionals’ beliefs and attitudes towards preconception care: a systematic review - Cherie Caut; Danielle Schoenaker; Erica McIntyre; Amie Steel (BMC Health Services Research)
Abstract Background Health professionals have previously identified various barriers and factors that would help facilitate preconception care services in healthcare settings. Clinically relevant preconception information and clinical practice guidelines have since been developed to aid health professionals in preconception care delivery. This systematic review aimed to (1) synthesise recent literature (past 8 years) describing health professionals’ beliefs and attitudes towards preconception care services or programmes and (2) determine if the experience of health professionals providing preconception care has changed compared to literature reviews conducted more than 8 years ago. Methods Five databases were searched between 27/01/2016 and 20/11/2024. Primary quantitative and qualitative research studies were included if they examined health professionals’ beliefs and attitudes towards delivering preconception care services or programmes. Study quality was assessed using the CASP Checklist (qualitative studies) and AXIS tool (quantitative studies). Data synthesis used thematic categorisation adapted from the framework approach. Results Twenty-seven studies were included (n = 11 qualitative, n = 14 quantitative, n = 2 mixed-methods studies). Methodological quality was generally good for qualitative studies but varied for quantitative studies. The results covered three categories: (1) addressing preconception care health literacy (i.e. lack of knowledge, awareness, training and resources), (2) clinical practicalities of preconception care (i.e. need for coordination of care and clarity on role responsibility), and (3) the role of the patient (i.e. need for public health education to support patient-led conversations). Conclusions Little has changed regarding the barriers and facilitators to providing preconception care reported by health professionals. To improve the provision of preconception care, there is a need to co-develop professional and public preconception health education, clinical resources, and a coordinated preconception healthcare service model.